Knowledge and practice of burn first aid among parents of under-age children - Halil, Mohd Fuad; Ibrahim, Nor Marini; Sidek Ahmad, Zulkhairul Naim; Che Hasan, Muhammad Kamil (Elsevier, 2021)
The objective of this study is to assess the level of knowledge and practice of burn first aid management among parents. A cross-sectional study was conducted among parents of under-age children in the Taman Desa Darul Naim area of Pasir Tumbuh, in Kelantan, Malaysia, using an adapted survey from Davies et al. Out of 80 respondents, 46.3% showed minimal knowledge of burn first aid, 47.5% had moderate knowledge, and 6.3% extensive knowledge. There was a significant relationship between the demographic data and the knowledge of burn first aid for gender (p = 0.02), but no significant relationship between the level of knowledge and level of education (p = 0.29) or age (p = 0.09). The findings indicate that the level of knowledge of burn first aid is limited. Education for parents of under-age children, including demonstrations of burn first aid, is needed to promote safe action and prevent further injury in the community.